Estimating the radiative forcing of carbonaceous aerosols over California based on satellite and ground observations. Issue 19 (4th October 2013) - Xu, Yangyang; Bahadur, Ranjit; Zhao, Chun; Ruby Leung, L.
Abstract [1] Carbonaceous aerosols have the potential to impact climate directly through absorption of incoming solar radiation and indirectly by affecting cloud and precipitation. Recent modeling studies have made great efforts to simulate both the spatial and temporal distributions of carbonaceous aerosol's optical properties and radiative forcing. This study makes the first observationally constrained assessment of the direct radiative forcing of carbonaceous aerosols over California. By exploiting multiple observations (including ground sites and satellites), we constructed the distribution of aerosol optical depths and aerosol absorption optical depths (AAOD) over California for a 10 year period (2000–2010). We partitioned the total solar absorption into individual contributions from elemental carbon (EC), organic carbon (OC), and dust aerosols, using a newly developed scheme. Our results show that AAOD due to carbonaceous aerosols (EC and OC) at 440 nm was 50%–200% larger than natural dust, with EC contributing the bulk (70%–90%). Observationally constrained EC absorption agrees reasonably well with estimates from global and regional chemical transport models, but the models underestimate the OC AAOD by at least 50%. We estimated that the top of the atmosphere (TOA) forcing from carbonaceous aerosols was 0.7 W/m2 and the TOA forcing due to OC was close to zero. The atmospheric heating of carbonaceous aerosol was 2.2–2.9 W/m2, of which EC contributed about 80–90%. We estimated the atmospheric heating of OC at 0.1–0.4 W/m2, larger than model simulations. EC reduction over the last two decades may have caused a surface brightening of 1.5–3.5 W/m2.